Need Analysis to Develop Arabic-Indonesian Translation Learning Model Based on Eco-Translatology Perspective - Ilham, Andri; Setiadi, Samsi; Failasuf, Chakam (Departemen Pendidikan Bahasa Arab, 2022)
Translation learning must be able to develop students' translation competence. One alternative model that can be developed is a translation learning model with an eco-translatology perspective which further optimizes the ecological environment of translation and student autonomy as learners. This study aims to determine student needs for developing translation learning models, especially Arabic-Indonesian translation, using an eco-translatology perspective. The method applied is a survey method with the instrument used is a questionnaire. The respondents involved were 65 students of the Arabic Language Education Study Program, Faculty of Languages and Arts, Universitas Negeri Jakarta, randomly. The study results prove that, generally, students still find it challenging to learn the translation. On the other hand, the learning model currently applied has not been able to fulfil their competence in translation. The implication is that the eco-translatology learning model that is more student-centered can be an alternative for learning Arabic-Indonesian translation.